Utilizing Wastewater Treatment Sludge in Mortar to Minimize the Carbon Footprints - Oo, Hein Htet; Daungwilailuk, Totsawat; Thongkong, Tanthong; Thongsom, Satchapat; Thonthan, Sujitra (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Cement production from the construction industry significantly contributes to global carbon emissions. Simultaneously, unsustainable sludge disposal methods from water treatment facilities have become an alarming threat to the environment nowadays. To tackle both issues, this research aims to investigate the potential of utilizing untreated wastewater treatment sludge (WWTS) as a partial cement replacement in mortars. Unlike previous studies that used energy-intensive treatment processes, this research emphasizes adopting untreated WWTS collected from the water quality control plant in Bangkok, Thailand, to enhance sustainability gains. In this study, five mortar mixes with WWTS replacement percentages of 0%, 5%, 10%, 15%, and 20% by weight of cement were prepared and tested. Physical properties of mortars were assessed by means of flowability and setting time. Mechanical performance of mortars was examined through compressive strength testing at 3, 7, and 28 days. Furthermore, a comparative analysis of carbon emissions between control mortar and WWTS-incorporated mortars was carried out in evaluating the environmental benefits of this study. By utilizing untreated WTS and analyzing its effects on mortar properties, the optimum replacement level of cement with WWTS that balances mortar’s performance and environmental benefits was determined. The findings of this study will contribute to sustainable construction practices by offering twofold benefits, not only in the reduction of cement consumption but also in providing an environmentally friendly solution for WWTS disposal.